Child abduction: prevention, investigation and recovery - Snow, Robert L. (Praeger, 2008)
Child abductions in the United States -- Sex offender abductions -- Infant abductions -- Psychotic abductions -- Family abductions -- International abductions -- Other types of child abduction -- Secondary victims of child abduction -- Why some children stay -- Police response to child abduction -- What the government can do -- What parents can do -- Helping victims of abduction recover -- Some final thoughts about child abduction -- Bibliography